Evaluating and tuning a static analysis to find null pointer bugs. - Hovemeyer, David
Using static analysis to detect memory access errors, such as null pointer dereferences, is not a new problem. However, much of the previous work has used rather sophisticated analysis techniques in order to detect such errors.In this paper we show that simple analysis techniques can be used to identify many such software defects, both in production code and in student code. In order to make our analysis both simple and effective, we use a non-standard analysis which is neither complete nor sound. However, we find that it is effective at finding an interesting class of software defects.We describe the basic analysis we perform, as well as the additional errors we can detect using techniques such as annotations and inter-procedural analysis.In studies of both production software and student projects, we find false positive rates of around 20% or less. In the student code base, we find that our static analysis techniques are able to pinpoint 50% to 80% of the defects leading to a null pointer exception at runtime.
Keywords: Theory of computation; Logics and meanings of programs; Semantics of programming languages; Program analysis; Experimentation; Measurement; Reliability; Static analysis; Testing